Survival of the fittest: Corporate control and the cleansing effect of financial crises - Rahul Mukherjee; Christian Proebsting (Graduate Institute of International and Development Studies, 2015)
How does the market for corporate control reallocate firm ownership in response to adverse aggregate financial shocks? To answer this question, we develop a tractable model of mergers and acquisitions (M&As) where firms facing different degrees of financial constraints acquire ownership of illiquid domestic firms. We show that acquisitions by financially constrained acquirers, on average, involve higher ownership stakes and post-acquisition survival rates when faced with adverse aggregate financial shocks, in comparison to acquisitions by unconstrained firms. This effect operates through two margins: An intensive margin (dominant for constrained acquirers) that works through a higher average productivity of acquirer-target matches, and an extensive margin (dominant for unconstrained acquirers) that operates thorough an increase in the proportion of fire-sale acquisitions in the economy. We provide evidence supportive of the predictions of the model in a large data set of M&As in emerging market economies. Our theoretical results provide insight into our novel empirical findings of a change in the degree of control acquired by and a convergence of survival rates between domestic and foreign acquisitions during financial crises, and point to the existence of a "cleansing effect" in the market for corporate assets.
Keywords: F21; G01; G34; 330; cleansing effect; financial crisis; financial shocks; cross-border mergers and acquisitions; capital reallocation